FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN OBJEK WISATA PELATIHAN GAJAH SEBELAT DESA SUKA BARU KECAMATAN MARGA SAKTI SEBELAT - Aprianty, Henny; Herlina, Aili; Alexsander, Alexsander (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to describe and understand the factors that influence the development of the Sebelat Elephant Training Tourism Object, Suka Baru Village, Marga Sakti Sebelat District. This study uses a qualitative approach. Data collection techniques through observation, interviews and documentation. The informants in this study were the Suka Baru Village Government and the PLG Management who managed the tourism object, and the community as tourists. The results of the study concluded that of the ten factors that influence the development of the Gajah Sebelat training tourist attraction in Suka Baru Village, Marga Sakti Sebelat District, 6 factors that have been well supported, namely tourists, tourist attraction, natural resources, prices, tourism organizations/perpetrators and regional characteristics while the other 4 factors namely accessibility, tourist facilities, human resources and information have not optimally supported the development of the Gajah Sebelat training tourism object, Suka Baru Village, Marga Sakti Sebelat District.